Ecotourism as a Tool for Mangrove Conservation - Friess, Daniel A. (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
Intertidal mangrove forests cover much of the coastline of Southeast Asia, provide crucial ecosystem services to millions of people living in the coastal zone, and are some of the most biodiverse in the world. However, they are one of the most threatened ecosystems in the tropics due to land cover conversion to agriculture (rice, oil palm) and aquaculture. Several conservation tools have been suggested to reduce mangrove deforestation, with many recent tools based on financially valuing the mangrove ecosystem and using that money to incentivize habitat protection. An important set of ecosystem services that can potentially be paid for under some settings are cultural values, such as recreation, tourism, spiritual value and aesthetic value. Ecotourism potentially represents a set of sustainable tourism principles that utilize the cultural ecosystem services of habitats to provide income to tourism operators and local communities. While we don’t yet have a comprehensive and large-scale overview of the full extent of mangrove ecotourism activities in the region, numerous case studies suggest the importance of these activities in bringing mangroves and people together. However, ecotourism must be implemented correctly in order to minimize the adverse impacts of tourists on local habitats. These impacts can be physical, including increased shoreline erosion, noise and pollution, or social, including the exclusion of local tour operators and communities. We need to understand these impacts, and how to reduce them, if we want to better conserve mangrove forests using neoliberal approaches such as ecotourism.